Kemajuan Teknologi Terbaru dalam Prosedur Deteksi Radiasi Nuklir: Tinjauan Literatur Sistematis - Putri Susanto, Azka Nabila; Muhammad Siddiq, Ikhsan; Muliyawati, Winda (Science, Tecnology, Religious, Economic, and Social Humanitis (STREAS), 2024)
In nuclear radiation detection procedures, there are various methods and instruments used to detect nuclear exposure, depending on the status of the nuclear radiation to be identified. This process involves the use of various methods and instruments adapted to the characteristics of the radiation being observed. In determining the appropriate method, factors such as radiation levels, radiation sources, types of particles involved, and the environment involved are important considerations. By considering these various factors, appropriate methodologies and relevant instruments can be applied to detect nuclear radiation with optimal precision and reliability. Among them: CMOS (Complementary Metal-Oxide-Semiconductor) cameras used in image capture respond directly to X-rays and gamma rays, development of CZT radiation detectors for nuclear power plant applications, scintillation detection which has attracted significant interest in various fields, such as nuclear medicine, nuclear radiation detection, high energy physics, and non-destructive inspection, A new approach has been proposed to detect underground nuclear explosions (UNEs) by monitoring the movement of natural radon isotopes (222Rn and 220Rn).